A New Generation of Intrusion Detection Networks - Krill, Jerry; O’Driscoll, Michael (Intelligent Sensor Networks, 2013)
The eight-pebble experiments successfully demonstrated swarming behavior; however, the reliability of the intrusion detection is difficult to fully evaluate. The prototype was used to demonstrate and validate the swarming behavior of a field of “pebbles” in a physical environment and to explore the effect of various sensing parameters and network configurations. The simulation was useful in testing the stability of the network. Critical to the affordability and scalability of the intruder sensor network concept is pebble technology that supports small size, low power consumption, and low cost. The time synchronization mode ensures that timers kept by all of the motes in the network are synchronized in order to get consistent real-time data. The CC2420 transceiver has features that enable a realistic simulation of the swarming pebbles network. An important aspect of the swarming network concept is the ability to achieve sufficient connectivity to the remote receiver that is monitoring the sensor field.